Early Onset Region and Cell Specific Alterations of Doublecortin Expression in the CNS of Animals with Sound Damage Induced Hearing Loss. (December 2019) - Freemyer, Andrea; Neal, Christopher; Nelson-Brantley, Jennifer; Staecker, Hinrich; Durham, Dianne
Highlights: Unilateral sound damage was used, survival time 25-30 days post damage Significant hearing loss at 5/7 tested frequencies Hearing loss related increases in DCX expression were observed in the cerebellum Hearing loss related decreases in DCX expression were observed in the hippocampus Abstract: Sound damage induced hearing loss has been shown to elicit changes in auditory and non-auditory brain regions. A protein critical for neuronal migration and brain development, doublecortin (DCX), has been used as a marker of central nervous system (CNS) neuroplasticity. DCX is expressed in unipolar brush cells (UBCs) of the dorsal cochlear nucleus (DCN), cerebellar parafloccular lobe (PFL) and neuronal precursor cells in the sub-granular zone of the hippocampal dentate gyrus (DG). Sound damage induced hearing loss has been shown to differentially impact DCX expression months later. To identify earlier alterations in DCX expression, we utilized immunohistochemistry to detect DCX protein in three brain regions (DCN, PFL, DG) approximately one month following unilateral sound damage. Auditory brainstem response was used to measure hearing loss. Unilateral hearing loss was evident in all sound damaged animals. Hearing loss related decreases in DCX expression were evident bilaterally in the DG while hearing loss related increases in DCX expression were evident bilaterally in the PFL. No changes to DCX expression were evident in the auditory DCN. Gap detection was used to assess whether this sound damage paradigm induced tinnitus-like behavior. However, results obtained from this behavioral test as used here were inconclusive and are presented here only as a guide to others wishing to design similar studies.